THE CORRELATION BETWEEN PERCEPTION AND HYPERTENSION EXERCISE ROUTINES ON THE QUALITY OF LIFE OF HYPERTENSIVE PATIENTS - Fathimatuzzahrah; Dwi Sri Handayani; Diah Nur Anisa (Keperawatan Anestesiologi Program Sarjana Terapan, 2024)
ABSTRACT (A single paragraph of about 250 words maximum. For research articles, abstracts should give a pertinent overview of the work. We strongly encourage authors to use the following style of structured abstracts, but without heading) Background: Poor quality of life in hypertensive patients can increase the risk of complications, highlighting the importance of finding effective strategies such as hypertension exercise to stabilize blood pressure. Perception also plays a crucial role in disease management. Methods: This quantitative study employed an analytical correlational design with a cross-sectional approach. A purposive sampling technique was used to select 100 participants based on inclusion and exclusion criteria. The questionnaire measured perceptions of hypertension exercise and quality of life among hypertensive patients. Statistical analysis was performed using Kendall Tau. Results: The majority of respondents had positive perceptions (72, 72.0%) and regularly performed hypertension exercises (74, 74.0%). The analysis showed no significant correlation between perception and the quality of life of hypertensive patients (p-value 0.177), but there was a significant correlation between exercise routines and quality of life (p-value 0.020). Conclusion: There is no significant correlation between the perception of hypertension exercise and the quality of life in hypertensive patients in Pojok V Hamlet, Minggir, Sleman. However, a significant correlation exists between hypertension exercise routines and quality of life. It is recommended that patients engage more actively in hypertension exercises to improve their quality of life. Future researchers are encouraged to explore different research models and subjects